The genetic secrets revealed from canine fetal fluids obtained in mid-pregnancy - S. Tal; G. Kahila Bar-Gal (Scientific Reports)
Abstract Amniotic fluid analysis is widely used for diagnostic and prognostic purposes in humans. However, its application in canine medicine remains underutilized, where genetic assessments typically rely on parental profiles. This study aimed to explore the potential for uncovering genetic information from canine fetuses during mid-pregnancy and its implications for future clinical management. Determining fetal sex, parental relationship, hereditary disorder profiles, and physical characteristics holds strong implications for breeders focused on canine welfare. The research involved six families from five breeds, with blood and fetal fluids collected from dams (n = 6), sires (n = 6), and conceptuses (n = 9) in the second trimester, as well as samples from newborn puppies (n = 6). Five candidate genes [AMELX/AMELY, MC1R, ABCB1, SOD1, and TLR4] were studied, and all samples were genotyped using StockMarks Canine Genotyping Kit. Comparison of fetal fluid and newborn puppy genotypes enabled coupling of the samples. Genetic data obtained from the fetal fluids, including hereditary disorders and physical characteristics, were then associated with the newborn’s profiles. The results demonstrated that fetal fluid analysis can determine the genetic profile of fetuses, offering valuable diagnostic and prognostic insights. These findings represent a proof-of-concept, establishing a foundational step toward integrating breeding program management and canine veterinary fetal care, pending further validation.